Clinical, Radiologic and Pathologic Evaluation of Gastrointestinal Stromal Tumors - Gemici, Ayşegül Akdoğan; Köneş, Osman; Kocataş, Ali; Cimilli, Ahmet Tan (Fırat University, 2013)
Objective: Gastrointestinal stromal tumors (GISTs) are the most common nonepithelial tumors of the gastrointestinal tract. GISTs occur anywhere along the gastrointestinal tract. Due to using radiological modalities often, we see the GİSTs more in our daily practice. We use radiologic modalities for not only making the diagnosis, also following the therapy and tumor progressions-relaps. Material and Method: In this study, 23 GISTs whose diagnosis and therapeutic surgical operations were made in our hospital between January 2007-January 2013, were evaluated retrospectively. Results: The ages of the cases ranged between 32 and 76 and the mean age were 58.70±13.67 years. 52.2% of the cases (n=12) were male and 47.8% of them (n=11) were female. 91.3% of the cases (n=21) were located at GIS and 8.7% of the cases (n=2) were located at non-GIS location. 30.4% of the cases (n=7) were metastatic. When the cases were evalulated in terms of their pathologic risk stratification systems, 39.1% of the cases (n=9) were in high risk group, 34.8% of the cases (n=8) were in intermediate risk group, 26.1% of the cases (n= 6) were in low risk group. The maximum diameter of the masses was 10.22 cm. 69.1% of the cases (n=13) showed luminal growth pattern and 38.1% (n=8) showed extraluminal growth pattern. 86.9% of the cases (n=20) had smooth borders, 13.1% of the cases (n=3) had irregular-invasive borders. Conclusion: Imaging is important for diagnosis, theraphy and follow -up. Computed tomography is the first choice for the radiologic evaluation. Also ultrasonography (US), magnetic resonance (MRI) and Flor18-deoxy-glucose positron emission tomography (FDG-PET) can be used in some cases.

Amaç: Gastrointestinal stromal tümör (GİST) gastrointestinal kanalın en sık görülen mezenkimal tümörüdür. Özofagustan rektuma kadar tüm gastrointestinal kanal boyunca izlenebilir. Günlük pratikte hastalara uygulanan radyolojik tetkiklerin artışıyla birlikte GİST'lere daha sıklıkla rastlanmaktadır. Sadece tümör tanısını koyarken değil tedavi etkilerini izlemede ve tümör progresyon-nükslerini takip etmede radyolojik modalitelere sıkça ihtiyaç duyulmaktadır. Gereç ve Yöntem: Bu çalışmada Ocak 2007- Ocak 2013 yılları arasında hastanemizde tanı konulan ve cerrahi tedavileri yapılan 23 GİST olgusu retrospektif olarak değerlendirildi. Bulgular: Olguların yaş dağılımları 32 ile 76 arasında değişmekte olup ortalama yaş 58.70±13.67'dir. Çalışmaya katılan hastaların % 52.2'si (n=12) erkek, % 47.8'i (n=11) kadındır. Lokalizasyon yeri incelendiğinde; 21 (% 91.3) olguda GİS, 2 (% 8.7) olguda ise GİS dışı olduğu görülmektedir. En sık lokalizasyon midedir. Araştırmaya katılan hastaların % 30.4'ünde (n=7) metastaz saptanmıştır. Omentum en sık metastaz yeri olarak izlenmiştir. Olguların risk grupları incelendiğinde; % 39.1'inin (n=9) yüksek, % 34.8'inin (n=8) orta ve % 26.1'inin (n=6) ise düşük risk grubunda olduğu saptanmıştır. Kitlelerin maksimum çapı 10.2 cm'dir. Kitlelerin % 69.1'i (n=13) lüminal büyüme paterni gösterirken, % 38.1'i (n=8) ekstralüminal büyüme paterni göstermiştir. Kitlelerin % 86.9'u (n=20) düzgün kenarlı iken % 13.1'i (n=3) düzensiz ve invaziv kenarlı izlenmiştir. Sonuç: Görüntüleme yöntemleri GİST'lerin tanı, tedavi ve takibinde önemlidir. Bilgisayarlı tomografi radyolojik değerlendirmede ilk seçenektir. Ayrıca ultrasonografi (US), manyetik rezonans (MRG) ve flor18-deoksi-glukoz pozitron emisyon tomografinin (FDG-PET) bazı durumlarda kullanılabilir.
Gastrointestinal Stromal Tümörlerin Klinik, Radyolojik ve Patolojik Bulgularının Değerlendirilmesi